Implementation Of Game-Based Learning Using Kahoot Application In Increasing Student Interest And Motivation - Salim, Salim; Muhammad Bagas F; Mohamad Aji Prasetia; Lubis, Muhammad Arif Fadhillah (Sean Institute, 2024)
In this era of rapidly evolving information and communication technology, approaches to learning also need to be adjusted to remain relevant and effective. One approach that is gaining popularity is the use of game-based learning, where game elements are used in the context of learning. Digital applications such as Kahoot are one of the tools that attract attention in the implementation of game-based learning. This study aims to explore the potential and effectiveness of game-based learning implementation using the Kahoot application in improving students' learning achievement at IT Indah Junior High School in Medan. The population in the research conducted had a total of 120 students. Meanwhile, the research sampling was conducted by utilizing the Krejcie and Morgan tables, resulting in 90 research samples. The results of the validity test of learning interest with learning motivation have a distribution of rcount > rtable. Meanwhile, the reliability test provides a description of the Alpha Cronbach results for each variable having a value greater than 0.6. The results showed a significant effect. The results of the study showed a sig value (2-tailed) of 0.000, meaning that the sig value <0.05, which means that the game-based learning method using the Kahoot application can increase student interest and motivation to learn at IT Indah Medan Junior High School.